Implementasi Manajemen Pembelajaran Daring di SD Nasional Plus BPK PENABUR Bogor - Laurentia Prabaniardi Kartikasari; Ari Novita Sari; Marina Sandra; Yari Dwikurnaningsih; Sophia Tri Satyawati (Jurnal Prakarsa Paedagogia, 2021)
The condition of the covid-19 pandemic has an impact on the learning management of an education. Where, this condition demands the implementation of online learning in all educational institutions. This study aims to provide an overview of the implementation of online learning management at SD Nasional Plus BPK PENABUR Bogor, related to the variety, problems and solutions that have been implemented. This study uses a survey method with data collection techniques through observation and interviews. The survey results show that the variety of online learning implemented at SD Nasional Plus BPK PENABUR Bogor is based on-based learning Computer Station, Collaborative Learning and Teacher Station with various methods. Researchers found the problems that arise can be handled well by the school.